Thyroid hormone and recovery of cardiac function in patients with acute myocardial infarction: A strong association? - Lymvaios, I.; Mourouzis, I.; Cokkinos, D.V.; Dimopoulos, M.A.; Toumanidis, S.T.; Pantos, C. (European Journal of Endocrinology, 2011)
Objective: This study investigated whether changes in thyroid hormone (TH) in plasma are associated with the recovery of cardiac function in patients with acute myocardial infarction (AMI). Previous experimental studies have provided evidence of potential implication of TH signaling in post-ischemic recovery of cardiac function. Methods: A total of 47 patients with AMI and early reperfusion therapy were included in this study. Myocardial injurywas analyzed by peak creatinine kinase-MB(CKMB) and cardiac function was assessed by echocardiographic left ventricular ejection fraction (LVEF%). Recovery of function (ΔEF%) was estimated as the difference of LVEF% between 48 h and 6 months (6 mo) after AMI. Total triiodothyronine (T3), thyroxine (T4), and TSH were measured in plasma at different time points (24 h, 48 h, 5 d, and 6 mo). Results: A significant correlation between LVEF% and T3 (r=0.5, P=0.0004) was found early after AMI (48 h), whereas no correlation was observed between CKMB and T3 (r=-0.04, P=0.81). A strong correlation was found between ΔEF% and total T3 (r=0.64, P=10-6) at 6 mo after AMI. Furthermore, multivariate regression analysis revealed that T3 at 6 mo (r=0.64, r2=0.41, P=10-6) was an independent determinant of DEF%. Conclusion: Changes in T3 levels in plasma are closely correlated with the early and late recovery of cardiac function after AMI. T3 levels at 6 mo appear to be an independent predictor of late functional recovery. © 2011 European Society of Endocrinology.